2010
DOI: 10.1016/j.ccr.2009.12.049
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchy of Self-Renewing Tumor-Initiating Cell Types in Glioblastoma

Abstract: The neural stem cell marker CD133 is reported to identify cells within glioblastoma (GBM) that can initiate neurosphere growth and tumor formation; however, instances of CD133(-) cells exhibiting similar properties have also been reported. Here, we show that some PTEN-deficient GBM tumors produce a series of CD133(+) and CD133(-) self-renewing tumor-initiating cell types and provide evidence that these cell types constitute a lineage hierarchy. Our results show that the capacities for self-renewal and tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
439
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(467 citation statements)
references
References 35 publications
21
439
1
6
Order By: Relevance
“…As CD133 was originally described as the NSC (Uchida et al, 2000) and BTIC (Singh et al, 2004) marker, its ability to exclusively isolate tumor-initiating cells has been debated in the literature, especially in adult glioblastoma. In this heterogeneous tumor, CD133À cells in long-term culture were found to be capable of tumor initiation in mice (Chen et al, 2010), although many recent publications maintain that not only is the CD133 þ fraction enriched in BTIC capacity Yan et al, 2011), but the features of 'stemness' marked by CD133 are associated with increasing malignancy and poor patient outcome (Bao et al, 2006;Thon et al, 2008;McCord et al, 2009;Pallini et al, 2010). In medulloblastoma, evidence more uniformly supports the application of CD133 as a BTIC marker, as CD133 þ multipotent NSCs were described in the postnatal cerebellum (Lee et al, 2005), and further studies showed that CD133 enriched for brain tumor-initiating capacity and radioresistance in primary and Daoy medulloblastoma-derived tumors (Fan et al, 2006;Blazek et al, 2007;Annabi et al, 2008Annabi et al, , 2010Pistollato et al, 2010;Yu et al, 2010).…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 94%
“…As CD133 was originally described as the NSC (Uchida et al, 2000) and BTIC (Singh et al, 2004) marker, its ability to exclusively isolate tumor-initiating cells has been debated in the literature, especially in adult glioblastoma. In this heterogeneous tumor, CD133À cells in long-term culture were found to be capable of tumor initiation in mice (Chen et al, 2010), although many recent publications maintain that not only is the CD133 þ fraction enriched in BTIC capacity Yan et al, 2011), but the features of 'stemness' marked by CD133 are associated with increasing malignancy and poor patient outcome (Bao et al, 2006;Thon et al, 2008;McCord et al, 2009;Pallini et al, 2010). In medulloblastoma, evidence more uniformly supports the application of CD133 as a BTIC marker, as CD133 þ multipotent NSCs were described in the postnatal cerebellum (Lee et al, 2005), and further studies showed that CD133 enriched for brain tumor-initiating capacity and radioresistance in primary and Daoy medulloblastoma-derived tumors (Fan et al, 2006;Blazek et al, 2007;Annabi et al, 2008Annabi et al, , 2010Pistollato et al, 2010;Yu et al, 2010).…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 94%
“…In the conditional knockout of the CD133 animal model, glioma can be formed from the cell population without CD133 expression (Nishide et al, 2009). In addition, both CD133-positive and CD133-negative human glioma-derived stem cell clones exhibit tumor formation ability (Chen et al, 2010). Some embryonic stem cell markers associated with glioma identification and aggressiveness, such as Oct4, Nanog, and Sox2, have been used for the guidance of glioma therapeutic selection (Ben-Porath et al, 2008;Holmberg et al, 2011;Shats et al, 2011).…”
Section: Molecular Markers Of Glioma Stem Cellsmentioning
confidence: 99%
“…Growing evidence supported that a subset of cancer cells, referred to as glioma stem cells (GSCs) or tumor initiating cells, are responsible for tumor propagation and recurrence in GBMs. [3][4][5] Although the cellular origin of GSCs remains controversial, 6 these cells have been demonstrated to share several typical features of embryonic or somatic stem cells (i.e., self-renewal capacity and multi-lineage differentiation potential). GSCs are privileged to drive tumor initiation and malignant progression.…”
mentioning
confidence: 99%